Управление рисками как конкурентное преимущество первичной медико-санитарной помощи городскому населению = Risk management as competitive advantage of primary health care for urban populations - Biryukov, V. S.; Chernomaz, V. Ts. (Journal of Education, Health and Sport, 2016)
Biryukov V. S., Chernomaz V. Ts. Управление рисками как конкурентное преимущество первичной медико-санитарной помощи городскому населению = Risk management as competitive advantage of primary health care for urban populations Journal of Education, Health and Sport. 2016;6(9):942-954. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.168414 http://ojs.ukw.edu.pl/index.php/johs/article/view/4013 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016. УПРАВЛЕНИЕ РИСКАМИ КАК КОНКУРЕНТНОЕ ПРЕИМУЩЕСТВО ПЕРВИЧНОЙ МЕДИКО-САНИТАРНОЙ ПОМОЩИ ГОРОДСКОМУ НАСЕЛЕНИЮ В. С. Бирюков, В. Ц. Черномаз Одесский национальный медицинский университет, Центр ПМСД №12 Приморского района г. Одессы РЕФЕРАТ Настоящее исследование посвящено внедрению инновационного метода управления – риск-менеджмента в деятельность медицинского учреждения первичного звена здравоохранения – Центра первичной медико-санитарной помощи №12 в г. Одессе. На основании рекомендаций международного стандарта ISO 9001:2015 в деятельности учреждения выделено 27 категорий рисков, сопровождающих 40 процессов и подпроцессов деятельности учреждения. Показан формализованный подход к оценке значимости рисков. Ключевые слова: риск-менеджмент, стандарт ISO 9001:2015, системы менеджмента качества, первичная медицинская помощь, медицинский аудит. RISK MANAGEMENT AS COMPETITIVE ADVANTAGE OF PRIMARY HEALTH CARE FOR URBAN POPULATIONS V. S. Biryukov, V. Ts. Chernomaz Odessa National Medical University, Center for Primary Health Care №12 of the Primorsky district of Odessa ABSTRACT The present study focuses on the introduction of innovative method - risk management in the activity medical institutions of primary health care - the Centre of primary health care №12 inOdessa. Based on the Recommendations of international Standard ISO 9001: 2015 was allocated to 27 risk categories in the activities of institutions, accompanying 40 processes and sub-processes of the institution. It was showed a formalized approach to assessing the significance of risks. Keywords: risk management, ISO 9001: 2015 quality management system, primary health care, medical audit.